Characteristics of AlGaN-based deep ultraviolet light-emitting diodes with a hole strengthened-injection layer. Issue 14 (16th August 2018) - Zhang, Xiu; Sun, Huiqing; Li, Zhifu; Wang, Xin; Liu, Tianyi; Guo, Min; Hou, Yufei; Guo, Zhiyou
Abstract: The optical and electrical properties of AlGaN-based deep ultraviolet light-emitting diodes (DUV LEDs) with the novel Mg-doping hole strengthened-injection layer (HSIL) are studied numerically and compared with conventional DUV LEDs. In this paper, two kinds of inserted layer of DUV LEDs have been investigated theoretically by the advanced physical model of semiconductor device (APSYS) software. The internal quantum efficiency, light output power, energy band diagrams, distributions of carrier concentration, radiative recombination rate and spontaneous emission intensity of three structures are calculated. The simulation results reveal that the carrier concentration and radiative recombination rates in the multiple quantum wells of DUV LEDs with HSIL are enhanced significantly. Moreover, the HSIL between EBL and p-doped region is able to reduce effective barrier height for holes in valence band, which is beneficial for hole injection from the p-doped region. As a result, the devices with HSIL, which is capable of alleviating the efficiency droop as the injection current increases, show excellent optical performance.